IMPLEMENTASI KEBIJAKAN TOLERANSI ANTAR UMAT BERAGAMA DI KOTA TOMOHON - ROGI, GABRIEL EDGAR YORDAN; POSUMAH, JOHNNY HANNY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2020)
The implementation of tolerance policy among religious people is not a stranger in Tomohon City, becausethe City was awarded as a pilot city for religious harmony in Indonesia. In its implementation, theGovernment does not yet have a local regulation that regulates the lives of religious people. Even though itwould be better if the local regulation was made as a reference in the implementation of strategic policiesrelated to tolerance between religious communities. In this study, the authors use the implementation modelfrom Smith, where policy implementation is seen from 4 aspects that have a major influence including theIdealized Policy, namely policies implemented in the form of programs in conjunction with the applicablelegal basis. Target groups are people or parties who are directly affected by existing policies and who haveto adopt patterns of interaction as expected by policy makers. Implementing Organization, namely theimplementing agencies or bureaucratic units of the Government in collaboration with the ReligiousInstitutions responsible for policy implementation. Environmental Factors are elements in the environmentthat influence or are influenced by policy implementation. This research uses descriptive qualitativeresearch methods, namely through 8 informant interviews, direct observation, and study documentation andassisted with interview guidelines, recording devices, and writing instruments. The results of the study ingeneral explained that the implementation of the policy of tolerance between religious communities inTomohon City has not been running optimally because the government does not yet have a RegionalRegulation that regulates the order of life of religious people.Keywords: Policy Implementation, Tolerance, Religious Peoples